2017
DOI: 10.18632/oncotarget.16735
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of the long non-coding RNA, SPRY4 Intronic Transcript 1, in patients with cancer: a meta-analysis

Abstract: Recent studies have emphasized the important role of long non-coding RNAs (lncRNAs) in cancer development. The present study performed a meta-analysis to investigate whether lncRNA, SPRY4 Intronic Transcript 1(SPRY4-IT1) can be served as a potential biomarker for prognosis in human cancers. The eligible studies were collected by searching multiple online databases (Pubmed, EMBASE, CNKI, Web of Science and Google Scholar) and meta-analysis was performed to explore the association between the expression levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
0
9
1
Order By: Relevance
“…In addition, we noticed that the expression of PANDAR is lower in NSCLC tissues compared with normal tissues and promoted PANDAR level can estimate better outcome in lung cancer, which was not consistent with most of other studies included in this meta-analysis [26]. Similarly, down regulation of lncRNA SPRY4-IT1 and TUG1 has been found to predict shorter OS in patients with NSCLC, which also contradicts with main conclusion in most other cancer studies [39][40][41][42]. The divergence was maybe ascribed to disease specific expression pattern of lncRNA instead of pute protein-coding genes, and it remains to be explored in future studies.…”
Section: Discussioncontrasting
confidence: 73%
“…In addition, we noticed that the expression of PANDAR is lower in NSCLC tissues compared with normal tissues and promoted PANDAR level can estimate better outcome in lung cancer, which was not consistent with most of other studies included in this meta-analysis [26]. Similarly, down regulation of lncRNA SPRY4-IT1 and TUG1 has been found to predict shorter OS in patients with NSCLC, which also contradicts with main conclusion in most other cancer studies [39][40][41][42]. The divergence was maybe ascribed to disease specific expression pattern of lncRNA instead of pute protein-coding genes, and it remains to be explored in future studies.…”
Section: Discussioncontrasting
confidence: 73%
“…Lung cancer produces the most lethal solid malignancies, and the role of lncRNAs in the genesis and development— and thus diagnosis and prognosis —of lung cancer has been widely studied [ 23 26 ]. In addition to the metastatic behavior of lung cancer, lack of precise and accurate biomarkers for diagnosis and prognosis may also contribute strongly to the low survival rate (< 15%).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, many meta-analysis articles, like our study, have been used to reveal the correlation of lncRNAs and cancer prognosis. Several lines of studies, meanwhile, have revealed that a lot of lncRNAs play a important role in cancer prognosis, such as TUG1, SPRY4, MALAT1 (Wang et al, 2015 , 2017 ; Yu et al, 2017 ). For instance, Wang et al found that SPRY4 is remarkably upregulated in various cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they performed the meta-analysis to examine the association between the SPRY4-IT1 expression level and prognosis in cancer patients. Finally, they suggested the prognostic role of SPRY4-IT1 in human cancers, and increased SPRY4-IT1 expression was closely associated with advanced features of human cancers (Wang et al, 2017 ). Likewise, NEAT1, as a novel lncRNA, has been recently found to be up-regulated in several cancers, contributing to tumor proliferation, apoptosis, metastasis and survival.…”
Section: Discussionmentioning
confidence: 99%